Moral Education Reflected in Siddarth P Malhotra’s Hickhi - Siti Fatimah; Trikaloka Handayani Putri (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
Moral education is developing students’ moral that can be developed by all out of school’s members and also school’s instrumentalities. This study aims to identify students’ moral and how the teacher developed students’ moral in Hickhi movie. In identifying moral education in Hickhi movie, researcher used John Dewey’s theory in 1922. This researcher used qualitative method. To collect the data, researcher identified and classified the scene reflected with the kind of moral education and the way to applied moral education. Research instrument was used observation sheet. The kind of moral education was found in Hickhi movie were moral formation and moral inquiry. According to John Dewey, moral formation had three characteristics, such as students’ non-cognitive, make a decision, and make a conclusion. Moral inquiry had two characteristics, such as adhere self-code of conduct and adhere other code of conduct. The way to applied moral formation that used by the teacher are praise and admonition, example and modeling, rule enforcement and boundary settings, and habituation and training. The way to applied moral inquiry was directive, non-directive. To teach moral formation and moral inquiry there were many strategies to applied them, such as teach the students in the sport center to know about the students closer, study outside to make the students happier, come to students’ house to see the real students’ conditions in their life. By great effort, the strategies used by Mrs. Naina to developed students’ moral were successful.